Challenging the shipper's location problem in port studies: An analysis of French AOC wine shipments to the US. (February 2021) - Guerrero, David; Thill, Jean-Claude
Abstract: One of the major issues in port choice and hinterland studies is the identification of the inland origins of containerized shipments. Firms' headquarters, intermediary cross-docking facilities, and the real places of origin of cargo are used interchangeably. This confusion may lead to a wrong perception of the factors affecting port choice decisions. This paper proposes a solution to overcome this problem, by focusing on shipments of French AOC wines ( Appellation d'Origine Contrôlée ) for which the geographical origin is strictly controlled. The paper also contributes to the port choice and hinterlands literatures by testing three new variables related to the logistical organization of shipments. A conditional logit model is employed to estimate the probability of choosing a port taking in account heterogeneity in the characteristics of shipments and decision makers. The results confirm the importance of inland distance and maritime connectivity, and bring new insight on the impact of logistical organization of shipments.